A7.16 Lack of Replication of PTPRC Gene as a Predictor of Response to Anti-Tumour Necrosis Factor Therapy in Patients with Rheumatoid Arthritis. (25th February 2013) - Canhão, Helena; Rodrigues, Ana; Santos, Maria Jose; Carmona-Fernandes, Diana; Costa, José; Santos, Helena; Branco, Jaime; Plenge, Robert; Solomon, Daniel; Armas, Jacome; António Silva, José; Fonseca, João Eurico; et al.
Abstract : Background and Objectives: A genome wide association study (GWAS) with Caucasian Northern European and North American rheumatoid arthritis (RA) patients and a replication study with English patients, pointed out for an association between PTPRC locus and response to anti-TNF drugs in RA. The Aim of our study was to evaluate whether this association is also verified in a population of Southern European (Portuguese) patients. Materials and Methods: We evaluated 383 RA patients from the Portuguese Rheumatic Diseases Register, Reuma.pt, for association between anti-TNF treatment response assessed by an absolute change in DAS28 at six months as the primary outcome and Rs10919563 PTPRC locus. We also studied the same association using the proportion of EULAR good responders and non responders at six months as the secondary outcome. Additive models were used taking the homozygote for the two major alleles as the reference variable. Univariate and multivariate linear and logistic regression analyses were performed, adjusting for clinical variables that influenced treatment response. Results: Taking the continuous primary outcome, univariate and multivariate linear regression adjusted for DAS28 and HAQ at baseline showed no association between change in DAS28 at 6 months and PTPRC locus (p-values of 0.72 and 0.69 respectively). Also univariate and multivariate logistic regression (good versus non-responders) did not depict any association with this SNP. Conclusions: In this replication study with a cohort of RA. Portuguese patients, we did not observe an association between Rs10919563 PTPRC locus and response to anti-TNF treatment.